ISLAM AND ECONOMIC DEVELOPMENT: The Contribution of Islamic Values in Encouraging Sustainable Economic Development - Sri Purwasih Simamora; Ismail; Attarikhul Kabir (Penerbit Merdeka Kreasi, 2023)
Economic development is an important agenda in improving people's welfare and creating social justice. However, the dominant conventional approach is often materially oriented towards the growth of the material, without considering the ethical and long-term sustainability dimensions. Islam as a comprehensive system of life offers a paradigm of economic development that integrates spiritual, social, and environmental aspects. This article aims to examine the contribution of Islamic values, especially monotheism, justice, and social responsibility in shaping a sustainable and inclusive economic development system. In addition, the strategic role of Islamic economic instruments such as zakat, waqf, infaq, and alms as pillars of wealth distribution and community empowerment was also discussed. Based on literature studies and conceptual analysis, it was found that Islamic economic values and instruments not only support economic growth, but also ensure equity, maintain social stability, and preserve natural resources. Therefore, the integration of Islamic economic principles into development policies is an important step to create a fair, dignified, and sustainable economic model. This study is expected to contribute to the development of economic development strategies that are more ethical and in accordance with the sharia maqashid.